Open house at the new Forsyth Memorial Hospital, 1964. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-22-64 p.1.
Open house at the new Forsyth Memorial Hospital, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth